A Patient Presenting with Cardiac Tamponade and the Challenges of Finding Its Cause: A Cardiac Angiosarcoma - Roshanak Habibi; Negar Faramarzi; Alvaro J. Altamirano; Shahriar Dadkhah (Case Reports in Cardiology)
Primary malignancies of the heart are so rare that most of the available data come from case reports or large single-center-based studies, with the overall incidence of 0.02% in the United States. Diagnosis in case of an isolated pericardial effusion as presentation is challenging, and determining that an angiosarcoma is even more challenging. Here, we presented a rare case of pericardial angiosarcoma which presented to us with tamponade. The patient eventually was diagnosed through pericardiectomy. A multimodality approach was attempted to treat the cancer. The clinical details of such a unique disease entity inspired us to present it as a case report.